The Structural Analysis of Marketing Innovations for Community Enterprise Products inPathum Thani Province, Thailand - Pattarapon Chummee (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Marketing innovation greatly affects marketing activities and affects the competitiveness of community enterprises create added value including the attractiveness of work. The objectives of this research are ( 1) to study the general characteristics of marketing innovations for community enterprises, (2) to observe factor of the marketing innovations for community enterprises and (3) to analyze the causal influence on marketing innovations for community enterprises. The research methodology used factor analysis and structural equation conceptual framework. The results from descriptive statistics showed that from the population of 324 sample size, it was found that the sample group was female at 165 or 50.6%, and there were between 11-20 employees, representing 63 people, or 19.3%. Most of them graduated with a bachelor's degree, numbering 148, representing 45.7%, age 42-50, 71 people, representing 21.9%, having opened for 7-10 years, with 86 cases being the largest number. 26.5 percent of the sample group operated the food business with the largest number of 80 cases, or 24.7%. The tolerance is between 0.627- 0.896 indicating that there is a low correlation influence does not cause correlation problems between variables. The VIF (Variance Inflation Factor) value is between 1.1160 -1.596. The structure equation is well suited, with Chi-square=175.26, df=110, P-value=0.000, RMSEA=0.051. New findings reveal a significant path between relationship between marketing innovation and competitive advantage. statistically important. Recommendations for entrepreneurs must develop new marketing innovations to build competitiveness, such as modern production innovations. New marketing channels through social media creating products for a variety of customer groups, especially the elderly, who are the demographic groups that need to pay special attention. For policy maker set policies in accordance with each community. Promote the production of unique products that are different from each other, not overlapping. Make your own community product stand out. Encourage the ability to export products to sell to foreign markets. Create and design packaging to create added value.